Size Exclusion Chromatography to Characterize DOC Removal in Drinking Water Treatment. - Allpike, Bradley; Heitz, Anna; Joll, Cynthia; Kagi, Robert; Abbt-Braun, G.; Frimmel, F.; Brinkmann, T.; Her, N.; Amy, G. (American Chemical Society, 2005)
A full-scale (110 ML/d) potable water treatment plant (WTP) based on the MIEX process, an innovative new process based on a strong base anion-exchange resin with magnetic properties, has been operating in Perth Western Australia since 2001. This plant has been configured so that a combined MlEX-coagulation (MIEX-C) process can be operated in parallel with a conventional enhanced coagulation (EC) process, allowing comparison of the performance of the two processes. Here, we report the use of size exclusion chromatography (SEC) to compare the removal of different apparent molecular weight (AMW) fractions of DOC by the two processes. Water was sampled from five key locations within the WTP, and SEC was carried out using three different on-line detector systems, DOC-specific detection, UV absorbance detection at lambda= 254 nm, and fluorescence detection (lambda(ex) = 282 nm; lambda(em) = 353 nm). This approach provided information on the chemical nature of the DOC comprising the various AMW fractions. The study showed that the MIEX-C process outperformed the EC process with greater removal of DOC in each of the eight separate AMW fractions identified. While EC preferentially removed the fractions of highest AMW, and those exhibiting the greatest aromatic (humic) character, MIEX-C removed DOC across all AMW fractions and did not appear to discriminate as strongly on the basis of differences in aromatic character or AMW. The results demonstrate the benefits of combining these complementary treatment processes. The study also demonstrates the utility of SEC coupled with multiple detection systems in determining the characteristics of various AMW components of DOC.